2017
DOI: 10.3389/fpls.2017.02043
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TCP Transcription Factors Interact with the SUMO Conjugating Machinery in Nuclear Foci

Abstract: In Arabidopsis more than 400 proteins have been identified as SUMO targets, both in vivo and in vitro. Among others, transcription factors (TFs) are common targets for SUMO conjugation. Here we aimed to exhaustively screen for TFs that interact with the SUMO machinery using an arrayed yeast two-hybrid library containing more than 1,100 TFs. We identified 76 interactors that foremost interact with the SUMO conjugation enzyme SCE1 and/or the SUMO E3 ligase SIZ1. These interactors belong to various TF families, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 85 publications
(135 reference statements)
5
44
0
Order By: Relevance
“…S1G), we conclude that SIM(-like) interactions also play a role in the SUMO-SCE1 interaction. Additional support comes from our recent work where we demonstrated that a conserved SIM-like motif in the N-terminal tail of SCE1 is essential for SUMO1 binding (Mazur et al, 2017). Our findings here suggest the same for SUMO-SIZ1 protein complexes in Arabidopsis, as previously reported for the homologous proteins from yeast and mammals (Cheong et al, 2010; Mascle et al, 2013; Kaur et al, 2017); however, functional mutants of the SIM domain in SIZ1 still need to be tested.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…S1G), we conclude that SIM(-like) interactions also play a role in the SUMO-SCE1 interaction. Additional support comes from our recent work where we demonstrated that a conserved SIM-like motif in the N-terminal tail of SCE1 is essential for SUMO1 binding (Mazur et al, 2017). Our findings here suggest the same for SUMO-SIZ1 protein complexes in Arabidopsis, as previously reported for the homologous proteins from yeast and mammals (Cheong et al, 2010; Mascle et al, 2013; Kaur et al, 2017); however, functional mutants of the SIM domain in SIZ1 still need to be tested.…”
Section: Resultsmentioning
confidence: 82%
“…Also in the BiFC assay, both the SCE1 SUM1 and SCE1 SIZ1 variants failed to interact with SIZ1, while the catalytic-dead variants (SCE1 CAT1 and SCE1 CAT2 ) still interacted with SIZ1. This suggests that SUMO loading in the catalytic site of SCE1 (SCE1 CAT1 and CAT2 ; E2∼ SUMO1) is not required for SCE1 and SIZ1 to interact, while the non-covalent interaction (SCE1 SUM1 ; E2 · SUMO1) strengthens this interaction in both the Y2H and BiFC assays (Fig 1F; Mazur et al, 2017). Apparently, the non-covalently bound SUMO acts as a glue in the SCE1-SIZ1 complex or it alters the SCE1 conformation such that it enhances the interaction between SCE1 and SIZ1.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations